ANALISIS REKONSILIASI FISKAL LAPORAN LABA KOMERSIAL GUNA MENYUSUN LABA FISKAL (STUDI KASUS DILAKUKAN PADA DPP BANK BPR JATIM TAHUN 2015) - Alexander, Kevin; Naruli, Akhmad; Rahayu, Puji (Jurnal Ilmiah Cendekia Akuntansi, 2022)
ABSTRACT The research was conducted in a company pension fund banking. The purpose of this study is to to analyze the fiscal reconciliation of commercial profit report to assist management in determining the fiscal profit in the period 2015. The variables used in this study are komerisial profit and fiscal profit. This study is expected as a medium to further deepen the knowledge in tax-related reconciliation into benchmarks or as a reference for further research. The existence of differences in commercial accounting principles with reference SAK with fiscal accounting with reference to the Tax Law, led to the emergence of differences in financial statements that resulted commercial accounting with taxation accounting, especially income statements as a determinant of the amount of corporate income tax.Therefore, to determine the amount of corporate income tax payable is required to make fiscal correction in the financial statements. The analytical technique used is to make a fiscal reconciliation report analyzing financial statement accounts and performing fiscal correction. Measures to measure the amount of profits in accordance with taxation or fiscal profit of principal determine the amount of taxable income (PhKP). From the result of the research, it is found that the original profit (loss) according to the company is Rp 3,917,022,203,76, - and profit according to fiscal is Rp 1,016,997,333,78, - there is difference of Rp 2,900,024,869,98, - which is obtained from net profit accordingly Commercial with net profit according to tax / fiscal regulations. From the results of this study determine the amount of taxable income (PhKP) of Rp 1,016,997,333,78, - as the basis of corporate tax calculations. ABSTRAK Penelitian ini dilakukan di perusahaan dana pensiun  perbankan. Tujuan dari penelitian ini adalah untuk untuk menganalisis rekonsiliasi fiskal laporan laba komersial untuk membantu manajemen dalam  menentukan laba fiskal pada periode 2015. Variabel yang digunakan dalam  penelitian ini adalah laba komerisial dan laba fiskal. Penelitian ini diharapkan sebagai media untuk lebih memperdalam pengetahuan dalam rekonsiliasi terkait perpajakan menjadi tolok ukur atau sebagai referensi bagi penelitian selanjutnya. Adanya perbedaan prinsip akuntansi komersial dengan acuan SAK dengan akuntansi fiskal dengan acuan UU perpajakan, menyebabkan timbulnya perbedaan laporan keuangan yang dihasikan akuntansi komersial dengan akuntansi perpajakan terutama laporan laba rugi sebagai penentu besarnya pajak PPh badan. Oleh karenanya, untuk menentukan besarnya pajak PPh badan yang terhutang perlu dibuat koreksi fiskal pada laporan keuangan. Teknik analisis yang digunakan adalah dengan membuat laporan rekonsiliasi fiskal menganalisis akun-akun laporan keuangan dan melakukan koreksi fiskal. Langkah untuk mengukur besaran laba yang sesuai dengan perpajakan atau laba fiskal tujuan pokoknya menetapkan jumlah penghasilan kena pajak (PhKP). Dari hasil penelitian diperoleh bahwa laba (rugi) semula menurut perusahaan adalah Rp 3.917.022.203,76,- dan laba menurut fiskal adalah Rp 1.016.997.333,78,-  terdapat selisih Rp 2.900.024.869,98,- yang diperoleh dari laba bersih sesuai komersial dengan laba bersih sesuai peraturan perpajakan/fiskal. Dari hasil penelitian ini menetapkan jumlah penghasilan kena pajak (PhKP) sebesar Rp 1.016.997.333,78,- sebagai dasar perhitungan pajak badan perusahaan.